Community-Based Economic Empowerment through Social Entrepreneurship: A Model for Sustainable Rural Development - Hikmat (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to develop a community-based economic empowerment model through a social entrepreneurship approach as a sustainable rural development strategy. The background of this research is based on the phenomenon of economic inequality and low independence of rural communities due to dependence on external assistance. The social entrepreneurship approach is seen as able to be an innovative solution because it combines social values with entrepreneurial principles that are oriented towards economic, social, and environmental sustainability. The research method used was mixed methods with an exploratory stage to explore local potential, followed by the implementation of a community-based participatory model in three pilot villages. Data were collected through in-depth interviews, participatory observations, and quantitative surveys that were analyzed descriptively and inferentially. The results of the study show that the implementation of community-based social entrepreneurship significantly increases economic capacity, social cohesion, and environmental sustainability of rural communities. The model developed focuses on collaboration between local governments, microfinance institutions, and community groups in building a fair and inclusive economic value chain. In addition, this model succeeds in fostering a spirit of social entrepreneurship that is oriented towards collective well-being, not just financial gain. These findings confirm that community-based economic empowerment through social entrepreneurship can be a strategic framework to strengthen rural economic resilience and support the achievement of the Sustainable Development Goals.